(untitled) (Al-Qalaa Journal, 2024)
The use of natural products is an essential way to new pharmaceutical leads for the discovery and development of new drugs to treat diseases. The present study was carried out to investigate the protective effects of propolis on aluminum-induced oxidative stress and biochemical alterations in rats. Therefore, the present experiment was undertaken to determine the effectiveness of propolis in alleviating the toxicity of aluminum chloride (AlCl3) on biochemical parameters of male Wistar Albino rats. Forty adult male albino rats were divided into four equal groups received treatment for 6 weeks: (GI) Control group received distilled water. (GII) Propolis group 50 mg/kg. (GIII) Aluminum chloride group 475mg/kg. (GIV) Propolis and aluminum chloride group. The AlCl3-treated group showed a significant increase in the activities of aspartate transaminase (AST), alanine transaminase (ALT) and total bilirubin in the plasma. Also, creatinine and urea, in the plasma were significantly increased while total protein was significantly decreased, propolis treatment with AlCl3 improved the biochemical and histological changes induced by AlCl3.